2014
DOI: 10.1080/10934529.2014.859025
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the removal of perchlorate when using single-walled carbon nanotubes (SWCNTs) or granular activated carbon: Adsorption kinetics and thermodynamics

Abstract: This study aims to remove perchlorate using single-walled carbon nanotubes (SWCNTs) or granular activated carbon (GAC). Dynamic and equilibrium adsorption experiments were performed to evaluate the thermodynamic behavior of perchlorate on SWCNTs and GAC. Key parameters affecting the adsorption, such as pH, ionic strength, and temperature were studied. The experimental results showed that the dynamic adsorption experiment achieved equilibrium in approximately eight hours. The adsorption capacity increased as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…During an ion exchange process, there are three main steps: (1) diffusion of species through a liquid film around resin particles (liquid film diffusion); (2) transfer of species through resin pores to places of ion exchange (particle diffusion); and (3) chemical reaction between species and resin functional groups (chemical reaction). Equations (8), (9), and (10), respectively can describe these three steps: 1214…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During an ion exchange process, there are three main steps: (1) diffusion of species through a liquid film around resin particles (liquid film diffusion); (2) transfer of species through resin pores to places of ion exchange (particle diffusion); and (3) chemical reaction between species and resin functional groups (chemical reaction). Equations (8), (9), and (10), respectively can describe these three steps: 1214…”
Section: Resultsmentioning
confidence: 99%
“…The Lagergren equation (see equation 7a) is one of the commonly used first-order kinetic equations, whereas the McKay equation (see equation 7b) is often used as second-order kinetic equation. [12][13][14] In addition, other kinetic models, such as the Elovich equation (see equation (7c)), Webber-Morris equation (see equation 7d Figure 7 shows fitting plots for these five models. From the fitting results (see Figure 7 and Correlation factor other equations.…”
Section: Kinetic Investigationmentioning
confidence: 99%
“…The extensive use of activated carbon for enhancing perchlorate removal has been reported. Mahmudov and Huang have showed that pristine activated carbon has moderate perchlorate uptake capacity compared with other major competing anions such as nitrate, sulfate and bicarbonates [33][34][35]. Increase in positive surface charge promotes the removal of anions while negatively charge surface enhances the removal of cations.…”
Section: Introductionmentioning
confidence: 97%